Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.

Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O-2 - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit (RSC Advances, 2015)
Activation of molecular O-2 by metal or metal oxide nanoparticles is an area of recent research interest. In this work, for the first time, we report that indium oxide nanoparticles of <3 nm size dispersed on mesoporous silica (TUD-1) can activate molecular O-2 and produce styrene epoxide with a selectivity of 60% and styrene conversion around 25% under mild conditions. It is found that neither indium oxide nor TUD-1 themselves respond to the styrene epoxidation reaction. The computational studies provide evidence that an oxygen molecule is highly polarized when it is located near the interface of both surfaces. The kinetic study shows that the reaction is of pseudo-first order and that the activation energy for styrene conversion is 12.138 kJ mol(-1). The catalysts are recyclable for up to four regeneration steps, with the styrene conversion and styrene epoxide selectivity almost unchanged.

Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15

Controlled surface/interface structure and spin enabled superior properties and biocompatibility of cobalt ferrite nanoparticles - Ansari, Sumayya M.; Sinha, Bhavesh B.; Pai, Kalpana R.; Bhat, Suresh K.; Ma, Yuan-Ron; Sen, Debasis; Kolekar, Yesh D.; Ramana, C., V. (Allied Surface Science, 2018)
High quality, crystalline, well-dispersed, and stable magnetic oxide nanoparticles (NPs) of inverse spinel cobalt ferrite (CoFe2O4; CFO) were prepared by a facile, reproducible, and simple hydrothermal route. The transmission electron microscopy, small-angle scattering and X-ray diffraction analyses demonstrate the structural quality of CFO NPs with a controlled size of similar to 12 nm. Small-angle scattering experiments demonstrate that the pristine CFO NPs have the individual size similar to 8.5 nm and spherical shape. The Raman and infrared spectroscopic measurements further confirm their high chemical quality and cubic symmetry. CFO NPs exhibit a remarkable, maximum coercivity (H-c) value of 18.92 kOe, which is the highest value achieved to date. Surface spins and spins canting along with a weak dipolar interaction accounts for the giant H-c and large effective anisotropy (11.45 x 10(6) erg/cm(3)) of these CFO NPs. The magnetic grain size of NPs reveals that the canted surface spins exist around the magnetic particles. Reorientation of surface spins and interparticle interaction causes the jumping behaviour in M-H hysteresis loops at H = 0. The cell viability of CFO NPs against the cancer (cisplatin resistant ovarian cancer - A2780/CP70) was evaluated to determine their potential application in biomedicine and health science. The mild response of CFO NPs in terms of their anti-proliferative nature against cancer cells and negligible cytotoxicity suggests their human-safe-and-friendly nature which makes them suitable for biomedical/health-related applications. Assessment of toxicity toward human red blood cells (RBC) revealed that hemolysis is less than 5% compared to the positive control confirming the potential applications of CFO NPs targeting human cells and making relevant for adopting them in biomedicine.

Characterizing microvoids in regenerated cellulose fibers obtained from viscose and lyocell processes - Sharma, Aakash; Sen, Debasis; Thakre, Shirish; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Regenerated cellulose fibers are among the most widely used bio-derived materials. Currently, there is great interest in transitioning from the traditional viscose process to the more environmentally friendly lyocell process for fiber production. Differences between the characteristics of viscose and lyocell fibers can be attributed to microstructural differences that arise due to differences in the processing techniques. Here, we use small-angle scattering to characterize the microvoids in regenerated cellulose fibers that might govern the onset of mechanical failure in these. In regenerated cellulose fibers, scattering of X-rays or neutrons at small angles is largely dominated by scattering from microvoids. We demonstrate that small angle X-ray scattering (SAXS) over the q range that is typical for most commercial instruments arises from Porod scattering from the microvoid surfaces, viz., the scattered intensity scales as q(-4). Therefore, it is not possible to extrapolate this data to lower q to obtain microvoid dimensions and volume fraction. We combine SAXS with medium-resolution small-angle neutron scattering to characterize the microvoids in regenerated cellulose fibers. Specifically, we compare fibers produced using the viscose process with those from the lyocell process. For both viscose and lyocell fibers, microvoids have a high aspect ratio and are elongated in the fiber direction. Also, the volume fraction occupied by the microvoids is comparable for viscose and lyocell fibers (0.04-0.05%). However, there are differences in the microvoid size: Microvoids are more highly oriented in lyocell fibers and have a larger average length and diameter compared with viscose fibers. This result might have important implications for understanding failure of these fibers.

Palladium impregnated amine Co-condensed hexagonal mesoporous silica: a novel catalyst in tailoring suzuki and heck coupling reactions in base free condition - Das, Prangya Paramita; Prabhakaran, Vinod C.; Nanda, Samik; Sen, Debasis; Chowdhury, Biswajit (ChemistrySelect, 2019)
Palladium impregnated amine co-condensed hexagonal mesoporous silicas (HMS-X) were synthesized (sol-gel process) using different amines (Ethylene diamine and pyridine) of various concentrations (0.25 equiv. and 2 equiv.). The effect of amine concentration on the local structure of hexagonal mesoporous silica was studied. The catalyst shows excellent catalytic activity and high TOF towards both Suzuki and Heck coupling reactions without using any base in reaction medium with the solvent DMF:water in (1:1) ratio. The catalyst was reused and it was recyclable up to three cycle without any appreciable loss of activity and the kinetics of the reaction varying different parameters also have been studied thoroughly.
Keywords: Amine functionalized silica; Base free; Heck reaction; Palladium supported catalysts; Suzuki reaction

Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR